Deteksi Mastitis Subklinis pada Peternakan Sapi Perah di Wilayah Kanigoro, Blitar - Afrilia, Tika Fitria Wulan; Faradila, Riska; Shofi, Ananda Rifqi; Arifianto, Ahmad Drajat (VITEK : Bidang Kedokteran Hewan, 2021)
Mastitis is an inflammatory of the udder internal tissue with different causes and degrees of severity, duration and diseases caused by vaiorus causative agent. This disease is very harmfull because it caused a reduction in milk production, the additional costs of medicines causing economic losses for farmers. This tesearch was a descriptive research. Detection was done by talking milk sampel on dairy cattle and was reacted with California Mastits Test (CMT) reagents which were circukated circuary for 10-15 seconds. This result about mastitis subklinis tested using by California Mastitis Test (CMT) in Kanigoro, Blitar. From 134 milk sampel showed 104 (76,4 %) samples positive mastitis subkkinis. The subclinical mastitis factor was influenced by cowshed management and milking of livestock, because sanitation and hygiene influenced to the level of bacterial contamination.